Evaluasi Kinerja Instalasi Pengolahan Air Limbah Farmasi PT. X - Kevin Leonardo Sulistiyo; Wahyu Ugroseno (Yayasan Literasi Sains Indonesia, 2025)
This article aims to evaluate the performance of the wastewater treatment plant (WWTP) operated by the pharmaceutical industry PT. X. The study assesses the effectiveness of wastewater treatment by testing water quality parameters from both the inlet and outlet, as well as analyzing each treatment unit, such as Oil and Scum Separation, Oil and Scum Collection, Equalization and Neutralization Tank, Aeration Tank, Clarifier, Break Tank, Filtration, Final Tank, and Sludge treatment units, including Sludge Collection and Stabilization Tank and Filter Press. Monitoring results show that PT. X’s wastewater meets the established quality standards. However, operational issues were observed, including overflow in the equalization and neutralization tanks, foam formation in the aeration tank, and sludge bulking in the clarifier unit, all requiring corrective actions. Recommended improvements include installing ultrasonic sensors, increasing dissolved oxygen (DO) concentration and the food-to-microorganism (F/M) ratio, and replacing filter media to optimize the treatment process. This evaluation is essential to ensure optimal wastewater treatment performance and compliance with environmental quality standards.